Aaptamine-related alkaloid from the marine sponge Aaptos aaptos - Toshiyuki Hamada; Yoshito Matsumoto; Phan, Chin Soon; Takashi Kamada; Satoaki Onitsuka; Hiroaki Okamura; Tetsuo Iwagawa; Naomichi Arima; Fumito Tani; Charles S. Vairappan (2019)
A new aaptamine-related alkaloid, 1,3-dioxolo [4,5-d] benzo [de]-1,6-naphthyridine (methylenedioxyaaptamine, 1), was isolated from the organic extracts of the Bornean marine sponge Aaptos aaptos, together with a known aaptamine derivative, 8,9,9-trimethoxy-9H-benzo [de]-1,6-naphthyridine (2). The structure of compound 1 was elucidated by interpretation of its spectroscopic data. Two compounds were tested for their cytotoxic potentials against adult T-cell leukemia (ATL) cells, and compound 1 showed moderate cytotoxic potential.